(untitled) (Research, Society and Development, 2022)
In order to solve the dental aesthetic pattern of a patient, who has dental stains on the enamel surface, we carried out this case report where are presented the steps employed for bleaching of teeth with superficial yellow/brown enamel stains with carbamide peroxide and micrometric removal of hard white enamel stains using the enamel microabrasion technique. The worn of dental surface during enamel microabrasion technique was measured with a digital analysis, using a intraoral scanner. It was observed a surprisingly esthetic outcome as the superficial enamel stains were camouflaged by the at-home dental bleaching. Only the superficial white enamel stains that remained evident were removed by enamel microabrasion technique with a minimal average wear of 118 um of the dental enamel on all anterior teeth, showing to be a conservative technique. Dental bleaching can solve the discoloration of vital teeth, such as the superficial yellow/brown hard enamel stains, as well as can mask the superficial white enamel stains. But when necessary, enamel microabrasion technique is an effective minimally-invasive option that can also be adopted.